Low Rank Coal Upgrading - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2001)
Kata Kunci: Coals US Department of Energy: Upgrading Low-Rank Coals, Encoal and Rosebud SynCoai Partnership, Clean Coal TechnoloiY (CCT). Topical Rqlort No. 10. Washington, D.C., August 1997